The Language of Engagement: Speech Functions and Mood in the Berkeley Exec Ed Podcast - Silaban, Jelly Prima Krisnawati; Azzahra, Sekar; Nurlela (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This paper investigates the interpersonal functions in the discourse of the Berkeley Exec Ed podcast, specifically the episode "The Science of Happiness & the Greater Good," using the Systemic Functional Linguistics (SFL) framework. It explores how language functions in interaction, conveys information, and entertains the audience by applying speech functions and mood types. A qualitative approach is used to analyze clause separations in the podcast transcript, which are then categorized based on speech functions—such as statements, questions, commands, and offers—and their corresponding moods: declarative, interrogative, and imperative. Most of the interactions (58.1%) are realized through statements using declarative moods. This trend indicates that the hosts aim to present information in a manner that is authoritative and informative, thereby building credibility and trust. Other functions include questioning (11.6%) and inviting (16.3%), which utilize interrogative and imperative moods, respectively, to encourage audience participation and engagement. This strategic interplay of linguistic elements demonstrates how speech functions and mood types contribute to the dynamism, interactivity, and effectiveness of the podcast discourse. The study highlights the crucial role of interpersonal language functions in fostering meaningful connections and maintaining audience interest in podcast formats. It also offers insights that can inform broader practices in media communication and content creation